Investigating neighbourhood assets and best friend attachment within a context of emotions among youth in a disadvantaged community in Kuala Lumpur - Nor Ba’yah Abdul Kadir,; Asmawati Desa,; Salleh Amat,; Nur Saadah Muhamad Aun,; Norhayati Ibrahim,; Hilwa Abdullah @ Mohd Nor, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The present study is among the first to investigate the neighbourhood assets and best friend attachment within a context of emotions among youth in a disadvantaged community in Kuala Lumpur. The aim of this cross-sectional study is to examine the positive and negative emotions in relation to neighborhood assets and best friend attachment in youth, who are living in communities known to have high levels of exposure to violence and to determine these factors as predictors of positive emotion and negative emotion. Using a convenience sampling technique, a total of 448 participants from low-income apartments in Kuala Lumpur, aged 13–24 years old were asked to complete a set of standardized questionnaires to measure neighbourhood assets, best friend attachment, and positive emotion and negative emotion. Multiple regression analysis revealed that two factors are the most significant predictors of positive emotion while four factors are the most significant predictors of negative emotion. The results suggested that the presence predictors of positive emotion can enhance the positive development of youth, however, the presence predictors of negative emotion must first be reduced to some extent to help these youths increase their emotional well-being.